A systematic mixed studies review of women's experiences of perineal trauma sustained during childbirth. (13th August 2018) - Crookall, Rebecca; Fowler, Gillian; Wood, Caroline; Slade, Pauline
Abstract: Aim: To explore the quantitative/qualitative literature on women's experiences of perineal trauma sustained during childbirth and the impact it may have on psychological/emotional well‐being. Background: Obstetric complications during childbirth can be a risk factor for postpartum psychological distress. Perineal trauma is one of the most frequent obstetric complications and it is important to understand any impact on psychological/emotional well‐being. Design: A convergent qualitative design using a hybrid deductive–inductive thematic synthesis approach to data transformation was used. Data sources: Web of knowledge, CINAHL, MEDLINE, AMED, PsyArticles, PsycInfo until May 2017. Review methods: Stage 1: transforming findings from the qualitative, quantitative and mixed methods studies into themes using thematic synthesis. Stage 2: integrating themes from the quantitative studies into those derived from the qualitative studies. Results: Records ( N = 2, 152) found of which 11 qualitative, 22 quantitative and 1 mixed methods were included in this review. Five themes were derived from thematic synthesis of qualitative studies "The mystery of perineal trauma", "The misery of perineal suturing", "The postnatal perineum", "Normalisation and feeling dismissed" and "Adjusting to a new normal—Coping and compromise" and five themes identified from the quantitative studies, experience of birth ( N = 4), sexual functioning ( N = 12), social functioning ( N = 2), psychological health ( N = 8) and quality of life ( N = 5). Conclusion: Perineal trauma can have a negative impact on psychological/emotional well‐being, however, the literature is conflicted and in need of clarification. Future research should clearly describe the perineal status of the women in the sample, use validated measures and consider the timing of such measures.